Fostering critical reflection in pre-service science teachers through video-based lesson analysis in South Africa - Thamae, Mamothibe; Sibanda, Doras; Naidoo, Jaqueline (Frontiers in Education, 2026)
IntroductionReflective practice is widely recognized as essential for effective teacher education, yet fostering deep, critical reflection among pre-service teachers remains challenging. In science education, where conceptual complexity and pedagogical demands intersect, reflection is crucial for bridging theory and practice. This study explores how video-based lesson analysis supports reflective engagement among pre-service physical science teachers in South Africa.MethodsA qualitative case study was conducted with 79 purposively selected pre-service teachers (45 PGCE and 34 BEd) from four higher education institutions. Participants analysed a video-recorded lesson on acids and bases and produced written reflections. Töman’s three levels of reflection (technical, application, and critical) served as the conceptual framework for analysis.ResultsFindings indicate limited engagement with critical reflection and a significantly higher incidence of “no reflection” among PGCE participants. Only 23 participants demonstrated coherent, detailed reflections across all three levels. Most reflections remained at technical and application levels, revealing a gap in higher-order reflective thinking.DiscussionThe results suggest that video-based analysis alone does not guarantee deep reflection. Without structured guidance and scaffolding, pre-service teachers tend to focus on surface-level observations rather than interrogating underlying pedagogical assumptions. This highlights the need for targeted strategies within teacher education programs to cultivate critical reflection as a core professional competency.ConclusionVideo-based lesson analysis offers potential for enhancing reflective practice, but its impact depends on deliberate integration of support mechanisms. Teacher educators and policymakers should prioritize structured reflection frameworks to prepare pre-service teachers for adaptive, inquiry-driven teaching.